Rheological Properties of Diesel-Based Fuels with Tyre Pyrolysis Oil as Admixture - Leszek Chybowski; Marcin Szczepanek; Tomasz Pusty; Piotr Brożek; Robert Pełech (Energies)
The aim of the article is to present the impact of blending diesel fuel with tire pyrolysis (TPO) oil on the changes in the fuel’s rheological properties and to evaluate these changes in the context of meeting legal requirements for various types of fuels. This research presents the impact of normative D100 diesel oil with TPO as an admixture on the rheological properties of the blends. Measurements are made for the content of TPO in the blend equal to 5, 7, 10, 15, and 20% m/m. In addition, the reference measurements are made for pure diesel oil and pure pyrolytic oil. Kinematic viscosity density, dynamic viscosity, viscosity index, pour point, cloud point, and cold filter plugging point are determined. The density of each sample is found at 15, 20, 30, 40, 50, 60, 70, 80, 90, and 100 °C. Viscosity is determined at the reference temperatures of 20, 40, and 100 °C, which are typically used as reference temperatures for petroleum products. Approximating models are built for all the analyzed parameters, which can be used in future studies. The fit of each model to empirical data is evaluated using the coefficient of determination R2. At the same time, the individual values of the analyzed indicators are compared to the limit values specified in selected standards and regulations, thus allowing us to assess the usefulness of individual fuels in terms of compliance with effective and reliable engine operation requirements. The fuels under study fulfill the normative requirements for the parameters for marine distillate fuels for blends with a pyrolysis oil content of 0–20% m/m and the requirements for standard-grade diesel oils indicated in the Regulation of the Minister of Economy of Poland for blends with a pyrolysis oil content of 0–7% m/m.